EMOSI KEAGAMAAN UMAT MUSLIM DI KOTA MEDAN TERHADAP PRODUK HALAL HPAI: PERSPEKTIF SOSIOLOGI AGAMA - Damanik, Putri Aulia Salsabila; Harahap, Suheri (Jurnal Sosial Humaniora, 2024)
This study aims to examine the religious emotions of Muslims in Medan City towards their decision in choosing HPAI halal products. In the perspective of sociology of religion, religious emotion is considered an important factor that influences consumption behavior, especially in the context of products related to religious adherence. HPAI halal products, as one of the main brands in the halal product market, offer religious values that are in line with consumers' spiritual needs and religious identity. This research uses qualitative method (field-research) with in-depth interviews and participatory observation to collect data from HPAI consumers in Medan City. The main focus of this study was to explore how emotions such as self-confidence, obedience, and spiritual satisfaction influence HPAI's halal product preferences and purchasing behavior. The findings show that religious emotions strongly influence customer purchases, with HPAI goods typically chosen because they are perceived to follow sharia and are close to Islamic ideals. The results of this study provide an overview of how religious identity influences market behavior among Muslims in Medan City and contribute to the sociology of religion in the consumption of halal products. This study can help halal product businesses to build better marketing strategies and better understand the dynamics of religion in consumer behavior